Endovascular parent vessel sacrifice in ruptured dissecting vertebral and posterior inferior cerebellar artery aneurysms: clinical outcomes and review of the literature. (3rd August 2015) - Madaelil, Thomas P; Wallace, Adam N; Chatterjee, Arindam N; Zipfel, Gregory J; Dacey, Ralph G; Cross, DeWitte T; Moran, Christopher J; Derdeyn, Colin P
Abstract : Background: Ruptured intracranial dissecting aneurysms must be secured quickly to prevent re-hemorrhage. Endovascular sacrifice of the diseased segment is a well-established treatment method, however postoperative outcomes of symptomatic stroke and re-hemorrhage rates are not well reported, particularly for the perforator-rich distal vertebral artery or proximal posterior inferior cerebellar artery (PICA). Methods: We retrospectively reviewed cases of ruptured distal vertebral artery or PICA dissecting aneurysms that underwent endovascular treatment. Diagnosis was based on the presence of subarachnoid hemorrhage on initial CT imaging and of a dissecting aneurysm on catheter angiography. Patients with vertebral artery aneurysms were selected for coil embolization of the diseased arterial segment based on the adequacy of flow to the basilar artery from the contralateral vertebral artery. Patients with PICA aneurysms were generally treated only if they were poor surgical candidates. Outcomes included symptomatic and asymptomatic procedure-related cerebral infarction, recurrent aneurysm rupture, angiographic aneurysm recurrence, and estimated modified Rankin Scale (mRS). Results: During the study period, 12 patients with dissecting aneurysms involving the distal vertebral artery (n=10) or PICA (n=2) were treated with endovascular sacrifice. Two patients suffered an ischemic infarction, one of whom was symptomatic (8.3%). One patient (8.3%) died prior to hospital discharge. No aneurysm recurrence was identified on follow-up imaging. Ten patients (83%) made a good recovery (mRS ≤2). Median clinical and imaging follow-up periods were 41.7 months (range 0–126.4 months) and 14.3 months (range 0.03–88.6 months), respectively. Conclusions: In patients with good collateral circulation, endovascular sacrifice may be the preferred treatment for acutely ruptured dissecting aneurysms involving the distal vertebral artery.